The relationship between forearm skin speed‐resolved perfusion and oxygen saturation, and finger arterial pulsation amplitudes, as indirect measures of endothelial function. (9th February 2018) - Bergstrand, Sara; Morales, Maria‐Aurora; Coppini, Giuseppe; Larsson, Marcus; Strömberg, Tomas
Abstract: Objective: Endothelial function is important for regulating peripheral blood flow to meet varying metabolic demands and can be measured indirectly during vascular provocations. In this study, we compared the PAT finger response (EndoPAT) after a 5‐minutes arterial occlusion to that from forearm skin comprehensive microcirculation analysis (EPOS). Methods: Measurements in 16 subjects with varying cardiovascular risk factors were carried out concurrently with both methods during arterial occlusion, while forearm skin was also evaluated during local heating. Results: Peak values for EPOS skin Perfconv and speed‐resolved total perfusion after the release of the occlusion were significantly correlated to the EndoPAT RHI (ρ = .68, P = .007 and ρ = .60, P = .025, respectively), mainly due to high‐speed blood flow. During local heating, EPOS skin oxygen saturation, S O 2, was significantly correlated to RHI (ρ = .62, P = .043). This indicates that S O 2 may have diagnostic value regarding endothelial function. Conclusions: We have demonstrated for the first time a significant relationship between forearm skin microcirculatory perfusion and oxygen saturation and finger PAT. Both local heating and reactive hyperemia are useful skin provocations. Further studies are needed to understand the precise regulation mechanisms of blood flow and oxygenation during these tests.